2000
DOI: 10.1021/jp9921710
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopy Studies of the Local Atomic and Electronic Structure of Iron Incorporated into Electrodeposited Hydrous Nickel Oxide Films

Abstract: We have utilized X-ray absorption fine structure (XAFS) spectroscopy to investigate the local atomic and electronic structure of iron incorporated into electrodeposited nickel hydroxide films. We found that cathodic codeposition from a solution containing Fe(II) and Ni(II) ions results in iron occupying Ni lattice sites in R-Ni(OH) 2 . The X-ray absorption near edge structure (XANES) shows that Fe is present as Fe(III) ions in the cathodically codeposited film. Analysis of the extended X-ray absorption fine st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 39 publications
10
83
2
1
Order By: Relevance
“…[ 46,47 ] However, shown in Figure 6 A, the most signifi cant increase in OER current density is obtained after the deposition of NiFe layer. For example, 600 mA cm −2 can be obtained at 1.55 V with NiFe/NiCo 2 O 4 /NF.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[ 46,47 ] However, shown in Figure 6 A, the most signifi cant increase in OER current density is obtained after the deposition of NiFe layer. For example, 600 mA cm −2 can be obtained at 1.55 V with NiFe/NiCo 2 O 4 /NF.…”
Section: Resultsmentioning
confidence: 95%
“…[ 17,47 ] However, the NiFe/NiCo 2 O 4 /NF composite electrode exhibits much higher OER activity than NiFe/NF electrode for bulk water electrolysis. This superior performance can be explained from the following aspects: First, the deposition of NiCo 2 O 4 nanofl akes layer increases the surface area dramatically, offering more catalytic active sites.…”
Section: Resultsmentioning
confidence: 99%
“…50−52 Choy et al 53 reported the change of Fe(III) to Fe(IV) in SrFeO 3 and associated high degree of covalence in Fe−O bond, which was further demonstrated experimentally by Abbate et al 54 Apparently, the edge shift is much smaller than ionically bonded Fe due to the high covalence. Balasubramanian et al 50 conducted the Fe K-edge XANES study on α-Fe, Fe-doped α-Ni(OH) 2 , α-FeOOH, and Fe-doped γ-NiOOH. Gradual edge shift toward higher and higher photon energies is observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[30][31][32] Four possible mechanisms of electrochemical deposition of Ni(OH) 2 from nickel nitrate solution have been proposed by MacArthur. [33] Furthermore, electrochemical deposition in Al 2 O 3 templates has recently been used to prepare inorganic micro-or nanotubes of Au, [34] Co, Fe, [35] Ni, [36] Cu, [37] Pt, [38] CdS, [39] and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The Fedoped Ni(OH) 2 tubes contain only Fe III because two binding energies of 725.3 eV and 711.1 eV were detected, which are assigned to Fe 2p 1/2 and Fe 2p 3/2 in Fe 2 O 3 , respectively. [42] Balasubramanian et al [32] reported that cathodic codeposition of Fe II with Ni II led to the incorporation of Fe in the Ni lattice sites of α-Ni(OH) 2 2 tubes shows that the atomic ratio of Fe to Ni is 1:3.7. Since Corrigan's study shows that iron/nickel hydrous oxides with this atomic ratio are very useful in lowering the Tafel slope for catalyzing the oxygen evolution reaction, [29] we believe that the Fe III -doped α-Ni(OH) 2 ·0.75H 2 O tubes have potential uses as electrocatalysts for alkaline electrolysis to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%